Anti-inflammatory terpenes from Schefflera rubriflora C. J. Tseng & G. Hoo with their TNF-α and IL-6 inhibitory activities. (July 2019) - Li, Fenghua; Zhang, Jian; Lin, Mingbao; Su, Xianming; Li, Changkang; Wang, Hongqing; Li, Baoming; Chen, Ruoyun; Kang, Jie
Abstract: The 95% ethanol extract and its EtOAc and n -BuOH fractions obtained from the leaves and twigs of Schefflera rubriflora C. J. Tseng & G. Hoo showed significant inhibitory activities (33.6%, 35.7% and 40.6%, respectively) against croton oil-induced ear inflammation in mice. Bioactivity-guided isolation and separation gave eight previously undescribed terpenes or terpene glycosides. Structural elucidation was based on UV, IR, and NMR spectroscopy, MS, experimental and calculated ECD data, and Mosher's method. To identify anti-inflammatory components from the extract, all the compounds were evaluated for tumor necrosis factor- α (TNF- α ) and interleukine-6 (IL-6) inhibitory activities. Four undescribed compounds inhibited mRNA expression of TNF- α and IL-6 with IC50 values of 15.3–52.4  μ M. Graphical abstract: Bioassay-guided fractionation of the 95% EtOH extract from Schefflera rubriflora led to the isolation and characterization of eight previously undescribed terpenes or terpene glycosides. Four of these compounds inhibited the mRNA expression of TNF- α and IL-6.Image 1 Highlights: Schefflera rubriflora twigs and leaves were extracted with EtOH and fractionated. Eight previously undescribed terpenes or terpene glycosides were isolated. Three of them are featured by dihydrophaseyl groups linked to phenolic glycosides. Two of them were elucidated by modified Mosher's method. Four terpenes or terpene glycosides exhibited TNF- α and IL-6 inhibitory activities.